Matrisome, innervation and oxidative metabolism affected in older compared with younger males with similar physical activity. Issue 5 (4th July 2021) - Lagerwaard, Bart; Nieuwenhuizen, Arie G.; Bunschoten, Annelies; de Boer, Vincent C.J.; Keijer, Jaap
Abstract: Background: Due to the interaction between skeletal muscle ageing and lifestyle factors, it is often challenging to attribute the decline in muscle mass and quality to either changes in lifestyle or to advancing age itself. Because many of the physiological factors affecting muscle mass and quality are modulated by physical activity and physical activity declines with age, the aim of this study is to better understand the effects of early ageing on muscle function by comparing a population of healthy older and young males with similar physical activity patterns. Methods: Eighteen older (69 ± 2.0 years) and 20 young (22 ± 2.0 years) males were recruited based on similar self‐reported physical activity, which was verified using accelerometry measurements. Gene expression profiles of vastus lateralis biopsies obtained by RNA sequencing were compared, and key results were validated using quantitative polymerase chain reaction and western blot. Results: Total physical activity energy expenditure was similar between the young and old group (404 ± 215 vs. 411 ± 189 kcal/day, P = 0.11). Three thousand seven hundred ninety‐seven differentially expressed coding genes (DEGs) were identified (adjusted P ‐value cut‐off of <0.05), of which 1891 were higher and 1906 were lower expressed in the older muscle. The matrisome, innervation and inflammation were the main upregulated processes, and oxidative metabolism was the main downregulated process in old compared with young muscle. Lower protein levels of mitochondrial transcription factor A ( TFAM, P = 0.030) and mitochondrial respiratory Complexes IV and II ( P = 0.011 and P = 0.0009, respectively) were observed, whereas a trend was observed for Complex I ( P = 0.062), in older compared with young muscle. Protein expression of Complexes I and IV was significantly correlated to mitochondrial capacity in the vastus lateralis as measured in vivo ( P = 0.017, R 2 = 0.42 and P = 0.030, R 2 = 0.36). A trend for higher muscle‐specific receptor kinase (MUSK) protein levels in the older group was observed ( P = 0.08). Conclusions: There are clear differences in the transcriptome signatures of the vastus lateralis muscle of healthy older and young males with similar physical activity levels, including significant differences at the protein level. By disentangling physical activity and ageing, we appoint early skeletal muscle ageing processes that occur despite similar physical activity. Improved understanding of these processes will be key to design targeted anti‐ageing therapies.